COMPARATIVE ANALYSIS OF CONSONANTS IN ENGLISH AND UZBEK LANGUAGES - Sharipova Yorqinoy (TADQIQOTLAR, 2025)
Abstract: The phonetic and phonological systems of languages play a fundamental role in shaping spoken communication, and consonants constitute one of the core components of these systems. A comparative analysis of consonants in different languages provides valuable insight into articulatory mechanisms, phonological organization, and language-specific sound patterns. This article presents a comparative analysis of the consonant systems of the English and Uzbek languages with the aim of identifying their similarities, differences, and distinctive phonological features. The study examines consonants from both articulatory and phonological perspectives, focusing on criteria such as place and manner of articulation, voicing, and phonemic distribution. Particular attention is given to consonant inventories, classification principles, and the functional load of consonant phonemes in both languages. The analysis reveals that while English and Uzbek share a number of common consonantal features, including plosives, fricatives, and nasals, they differ significantly in terms of the number of phonemes, the presence or absence of certain consonant types, and the role of secondary articulatory features. Special emphasis is placed on consonants that pose difficulties in second language acquisition, such as interdental fricatives in English and uvular or affricate sounds in Uzbek. The study also considers phonotactic constraints, allophonic variation, and the influence of consonant clusters on pronunciation patterns. These differences are shown to reflect broader typological distinctions between the two languages, as well as their historical and phonological development.